Development of Combat Armor From Ramie-Aramidpolyester Composite - Radif, Zainab Shaker (2009)
In this study the laminates composite material is developed from ramie-aramid-polyester resin. The aim of this study is to developed solid body armor by using ramie-aramid reinforced polyester composite structure design. The design of body armor meet the specific requirements of ballistic resistance. The matrix of the developed composite is unsaturated Polyester resin reinforced with aramid-natural ramie fiber. This ramie-aramid composite is subjected to high impact loading. The target is shot by using gas gun machine supported by camera hardware to capture the projectile speed. To achieve the goal of the research, experiments were conducted with a focus on estimation the ballistic limit, maximum energy absorption, composite failure mode, life time rupture, target geometry and environmental effect. The results of these experiments indicated that the maximum ballistic limit validated at impact speed is in the range of 250 m/s to 656.8 m/s for the second protection level. The targets are improved in the area of impact respond with increase in the relative humidity in the range of 50% ± 20%.Whereby, reduction of resistance results in the increase of temperature. The range of temperatures was between 20 OC to 70 OC. A limited delamination was generated under multiple shots. Targets geometry plays a main role in increasing impact response. Hence, the results were presented high resistant impact for pairs from panels with total thickness of 15 mm ± 3mm. This body armor is one of most economical armor products in that; common materials were used in its production especially to the reduction of the using Kevlar amount that led to decrease in its cost. On the other hand this armor met the ballistic threats under 623 m/s of 15 mm ± 3 mm target thickness and 837.5 m/s of 25 mm ± 2.mm. Thus, the armor is equivalent to third level of protective ballistic limits in National Institute of Justice (NIJ) standards